2012
DOI: 10.1089/apc.2012.0135
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial of Raltegravir Replacement for Protease Inhibitor or Non-Nucleoside Reverse Transcriptase Inhibitor in HIV-Infected Women with Lipohypertrophy

Abstract: Lipohypertrophy in HIV-infected patients is associated with metabolic abnormalities. Raltegravir (RAL) is not known to induce fat changes or severe metabolic perturbations. HIV-infected women with central adiposity and HIV-1 RNA less than 50 copies per milliliter on non-nucleoside reverse transcriptase inhibitor (NNRTI)-or protease inhibitor (PI)-based antiretroviral therapy (ART) continued their nucleoside reverse transcriptase inhibitor (NRTI) backbone and were randomized to switch to open label RAL immediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 26 publications
1
34
0
3
Order By: Relevance
“…Total cholesterol levels improved in the Switch Group, which corroborates findings from previous studies assessing switches from protease inhibitors 15, 19, 20 or EFV 20 to RAL. Similar findings in ART-naïve studies comparing RAL to EFV showed less effects of RAL on lipid profiles.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Total cholesterol levels improved in the Switch Group, which corroborates findings from previous studies assessing switches from protease inhibitors 15, 19, 20 or EFV 20 to RAL. Similar findings in ART-naïve studies comparing RAL to EFV showed less effects of RAL on lipid profiles.…”
Section: Discussionsupporting
confidence: 89%
“…20 We also explored potential changes in sCD14 and sCD163 as markers of monocyte activation with switch to RAL. Greater sCD14 levels have been linked to an increased risk of death 25 while higher sCD163 levels have been associated with worsening inflammatory atherosclerotic disease in those with HIV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Lipodystrophy causes a redistribution of fat and unusual changes in body habitus such that there is an increase in abdominal girth; the appearance of ''fat padding'' or ''buffalo hump'' on the back of the neck; enlarged breasts in both men and women; and thinning and wasting of subcutaneous fat tissue of the arms, face, and buttocks. 1,2 The reason for the development of lipodystrophy in HIV-infected people is most likely multifactorial and related to immune depletion and immune recovery, antiretroviral medications, dysregulation of fatty acid metabolism, hormonal influences, and individual genetic predispositions. NonYHIV-related factors include female sex, older age, diet, and obesity.…”
Section: Body Habitus Changesmentioning
confidence: 99%
“…[29] Telmisartan is an angiotensin receptor blocker (ARB) and partial PPAR-γ agonist with potential metabolic and anti-inflammatory benefits,[30,31] including improvements in visceral adipose tissue (VAT) volume, fasting glucose and lipid profiles, and markers of oxidative stress and vascular inflammation in primarily HIV-uninfected populations. [3235] The Metabolic Abnormalities, Telmisartan, and HIV Infection (MATH) trial was a pilot study designed to assess the effects of 24 weeks of telmisartan on visceral adiposity and metabolic parameters in HIV-infected participants with central adiposity on suppressive ART.…”
Section: Introductionmentioning
confidence: 99%